ANGKOLA: Experience Learning Model for Elementary Schools - Hamidah, Hamidah; Lubis, Maulana Arafat; Azizan, Nashran (Journal of Integrated Elementary Education, 2025)
Indonesia is known as a country rich in culture. Therefore, in elementary school learning, it is very important to introduce their cultures, so that students can preserve them in the future. The objective of this research is to design a valid, practical, and effective ANGKOLA Model for teaching Pancasila and Civic Education to elementary school students in Padangsidimpuan City. This model is designed to integrate local Angkola cultural values ​​in the learning process so that students can understand the material contextually and meaningfully. The research method used is development research with the Plomp model, which consists of several stages, namely initial investigation, design, realization, testing, evaluation, and revision. This research was carried out in three elementary schools located in Padangsidimpuan City, involving fourth-grade students as the research sample. Data collection was carried out through various techniques, including observation, tests, questionnaires, and interviews, to obtain comprehensive information regarding the validity, practicality, and effectiveness of the learning model developed. The collected data were examined through both a quantitative and qualitative approach. Findings reveal that the model demonstrates strong validity as confirmed by expert evaluations, offers practical use due to its ease of implementation by both teachers and students, and proves effective in enhancing students’ comprehension of Pancasila and Civic Education content. The model also contributes to improving students' critical thinking skills through an experiential and local culture-based learning approach. The implications of this study indicate that the use of local culture-based learning models can improve the quality of learning in elementary schools.